Милош и Россия - Ушинскене, Виктория (Slavistica Vilnensis, 2011)
Viktorija Ušinskienė Milosz and Russia The article presents the writer’s views on Russia found in his key pieces, such as Russia. A trans-oceanic point of view, Family Europe and some others. Milosz takes on ideas that shaped Russian culture as uniquely expressed in the literary, philosophic and religious thinking of the late 19th–20th century. The person of F.Dostoyevsky is in focus of Milosz investigations.